Spatial heterogeneity of soil factors enhances intraspecific variation in plant functional traits in a desert ecosystem - Wang, Yong-chang; Zhang, Xue-ni; Yang, Ji-fen; Tian, Jing-ye; Song, Dan-hong; Li, Xiao-hui; Zhou, Shuang-fu (Frontiers in Plant Science, 2024)
IntroductionFunctional traits of desert plants exhibit remarkable responsiveness, adaptability and plasticity to environmental heterogeneity.MethodsIn this study, we measured six crucial plant functional traits (leaf carbon, leaf nitrogen, leaf phosphorus, leaf thickness, chlorophyll concentration, and plant height) and employed exemplar analysis to elucidate the effects of soil environmental heterogeneity on intraspecific traits variation in the high-moisture-salinity and low-moisture-salinity habitats of the Ebinur LakeWetland National Nature Reserve.ResultsThe results showed that (1) The soil moisture and electrical conductivity heterogeneity showed significant differences between the two moisture-salinity habitats. Moreover, soil nutrient in high moisture-salinity habitat exhibited higher heterogeneity than in low moisture-salinity habitat. The order of intraspecific trait variation among different life forms was herbs > shrubs > trees in both the soil moisture-salinity habitats. (2) At the community level, intraspecific variation of leaf carbon, nitrogen, plant height and chlorophyll content in high moisture-salinity habitat was higher than that in low moisture-salinity habitat, while the opposite was true for leaf thickness and leaf phosphorus content. (3) Our findings revealed a positive impact of soil heterogeneity on intraspecific traits variation. In high moisture-salinity habitat, the heterogeneity of soil organic carbon had the highest explanatory power for intraspecific traits variation, reaching up to 20.22%, followed by soil total nitrogen (9.55%) and soil total phosphorus (3.49%). By comparison, in low-moisture-salinity habitat, the heterogeneity of soil moisture alone contributes the highest explanatory power for intraspecific traits variation in community-level, reaching up to 13.89%, followed by the heterogeneity of soil total nitrogen (3.76%).DiscussionThis study emphasizes the differences in soil heterogeneity and intraspecific trait variation among plant life forms under various soil moisture-salinity habitats and confirms the significant promoting effect of soil heterogeneity on intraspecific trait variation of desert plant. Our findings provide valuable theoretical basis and reference for predicting plant adaptation strategies under environmental change scenarios.